What does the future look like - home hemodialysis - Buczek, Weronika; Wiśniewski, Mikołaj; Oleszczuk, Rafał; Kozińska, Iga; Oleszczuk, Anna; Grzebalska, Agnieszka M. (Journal of Education, Health and Sport, 2022)
Home hemodialysis (HHD) is a discovery from 1961 that is now experiencing a revival. It is a convenient and modern method of renal replacement therapy that allows the patient to undergo hemodialysis sessions at home. Due to the growing interest in home hemodialysis, we decided to present the potential of this renal replacement method, show both its benefits and complications resulting from its use. Undoubtedly, HHD has many benefits resulting mainly from the possibility of regulating the duration of the sessions and increasing their frequency. However, this method is also burdened with numerous complications. There are training courses in the use of HHD for patients who have just been diagnosed with end-stage renal disease as well as for patients undergoing dialysis using other methods. Appropriate patient selection is an important factor for the success of home therapy. There is a fierce battle in the home hemodialysis machine market. Manufacturers are outdoing each other in innovative technologies to ensure ease of use, trouble-free operation and minimize complications. The costs of home hemodialysis include more components than the dialysis treatment itself. Home hemodialysis gives patients comfort and independence above all. This is part of nephrology that undoubtedly requires a lot of work and development, but is certainly an invention of the 21st century.